Agreement among HLA antibody detection assays is higher in ever-pregnant donors and improved using a consensus cutoff - Carrick, Danielle M.; Johnson, Bryce; Kleinman, Steven H.; Vorhaben, Robert; Chance, Suzette C.; Lee, Jar-How; Roback, John D.; Pandey, Suchitra; Sun, Yu; Busch, Michael P.; Norris, Philip J. (Transfusion (Philadelphia, Pa.), 2011)
BACKGROUND: HLA antibodies might contribute to the pathogenesis of transfusion‐related acute lung injury (TRALI). HLA antibody detection methods include ELISA, flow cytometry, and multiplex bead‐based assays, as well as the older lymphocytotoxicity assay, and it is not obvious how to compare results across platforms. STUDY DESIGN AND METHODS: Five hundred twenty‐five serum samples were selected from 7841 donors in the Leukocyte Antibody Prevalence Study (LAPS) repository based on risk for the development of HLA antibodies, using the number of pregnancies as the risk factor. Subjects included 81 males and females with 0 (n = 187), 1 (n = 67), or 2+ pregnancies (n = 190). Replicate frozen serum aliquots were sent blinded to four different HLA antibody assay manufacturers for detection using five different assays. RESULTS: The flow cytometry and multiplex bead based‐assays typically resulted in a larger proportion of HLA antibody positive samples compared with ELISA based assays. Latent variable analysis was used to derive a new set of consensus cutoffs, which yielded similar sensitivities across test platforms and increased concordance amongst assays. Assay agreement was higher in ever pregnant females than in males and never‐pregnant females. CONCLUSIONS: Different assays resulted in varied positivity rates when the manufacturer's suggested cutoffs were used, demonstrating that care needs to be taken when comparing clinical outcomes data generated using different HLA antibody assays and testing platforms. The method used here, involving latent variable analysis, presents one possible approach to calculating comparable cutoffs that result in broad agreement across assays with respect to positivity designation.